Non-native populations of an invasive tree outperform their native conspecifics - Hirsch, Heidi (2016)
Introduced plants often face new environmental conditions in their non-native ranges. To become invasive, they need to overcome several biotic and abiotic filters that may trigger adaptive changes in life-history traits, like postgermination processes. Such early life cycle traits may play a crucial role in the colonization and establishment success of invasive plants. As a previous study revealed that seeds of non-native populations of the woody Siberian elm, Ulmus pumila, germinated faster than those of native populations, we expected growth performance of seedlings to mirror this finding. Here, we conducted a common garden greenhouse experiment using different temperature and watering treatments to compare the biomass production of U. pumila seedlings derived from 7 native and 13 populations from two non-native ranges. Our results showed that under all treatments, non-native populations were characterized by higher biomass production and enhanced resource allocation to aboveground biomass compared to the native populations. The observed enhanced growth performance of non-native populations might be one of the contributing factors for the invasion success of U. pumila due to competitive advantages during the colonization of new sites.